Integration of clinical simulation into a post-registration neurological course: Insights from the students on the use of a flexible approach to debriefing (Journal of Applied Learning and Teaching, 2024)
Background: This hermeneutic-phenomenological study explored the integration of simulation-based training and flexible debriefing techniques within a post-registration neurological course for registered nurses. It aimed to understand the potential of these teaching strategies to enhance clinical skills and encourage confidence in neurological practice.Aim: The research sought to explore the lived experiences of post-registration neurological nursing students, emphasising their interaction with clinical simulation and flexible debriefing methods to enhance their learning experiences.Methods: Adopting a hermeneutic-phenomenological research design, the study examined the experiences of ten registered nurses, gathering data through semi-structured interviews and focus groups. The resultant data offered a rich understanding of their engagement with the simulation-based course.Findings: The thematic analysis of the data revealed four dominant themes: (1) self-evaluation and critique, (2) group discussion and collective learning, (3) confidence building, and (4) interface of theory and practice. These themes provided a nuanced understanding of the participants’ experiences with the course and its pedagogical strategies.Conclusion: The findings accentuated the transformative role of high-fidelity simulation, complemented with flexible debriefing techniques, in enhancing the participants’ self-confidence, neurological knowledge, and clinical skills. Despite some challenges relating to reconciling student expectations with the reality of mannequin-based simulation, these insights illuminate the intrinsic value of flexible debriefing as a pivotal tool in supporting other pedagogical strategies, thereby enriching the overall student experience within this post-registration neurological course.